Pharmacokinetics and tolerability of IDP-73152 mesylate after a single oral administration under fasted and fed conditions in healthy volunteers - Shin D; Park SI; Lee HS; An KM; Jung J; Lee M; Yu KS (Dove Medical Press, 2019)
Dongseong Shin,1–3 Sang-In Park,4,5 Hong-Sub Lee,6 Kyung-Mi An,6 Juyoung Jung,6 MyongJae Lee,6 Kyung-Sang Yu31Department of Pharmacology, Gachon University College of Medicine, Incheon, Korea; 2Clinical Trials Center, Gachon University Gil Medical Center, Incheon, Korea; 3Department of Clinical Pharmacology and Therapeutics, Seoul National University College of Medicine and Hospital, Seoul, Korea; 4Department of Clinical Pharmacology and Therapeutics, Kyung Hee University Hospital, Seoul, Korea; 5East-West Medical Research Institute, Kyung Hee University, Seoul, Korea; 6Research Laboratories ILDONG Pharmaceutical Co. Ltd, Hwaseong, KoreaBackground and objective: IDP-73152 mesylate is a peptide deformylase inhibitor under investigation for the treatment of complicated skin and respiratory tract infections. The objective of this study was to investigate the pharmacokinetic (PK) profile and tolerability of IDP-73152 and the effect of food after a single oral administration.Methods: A dose block-randomized, double-blind, placebo-controlled, dose-escalation study was conducted. A total of 56 healthy volunteers received IDP-73152 mesylate in a single oral dose of 40, 80, 160, 320, 640, or 1280 mg in the fasted and fed (640 mg only) states. Blood and urine samples for PK analysis were collected up to 48 h post dose.Results: The area under the plasma concentration-time curve (AUC0-t) of IDP-73152 increased in a dose-proportional manner in the range of 40–320 mg. The mean terminal half-life decreased from 10.7 to 6.2 hrs as the dose increased. The fraction excreted unchanged in the urine ranged from 0.05 to 0.12. In the 640-mg dose group, food delayed the median time to peak concentration (tmax) from 0.9 to 3.5 hrs. Furthermore, the maximum plasma concentration (Cmax) were decreased by 36.2%; however, AUC0-t was not generally affected. No serious adverse event or clinically significant findings were observed.Conclusions: The systemic exposure of IDP-73152 proportionally increased as the dose increased up to 320 mg. The rate of absorption and extent of exposure were reduced by food intake. IDP-73152 was well tolerated without clinically significant adverse effects after a single oral administration.Keywords: phase I, pharmacokinetics, antibiotics, peptide deformylase inhibitor